Microbunch instability observations from a THz detector at diamond light source - Shields, W; Bartolini, R; Boorman, G; Karataev, P; Lyapin, A; Puntree, J; Rehm, G (2012)
Diamond Light source is a third generation synchrotron facility dedicated to producing radiation of outstanding brightness, ranging from infra-red to x-rays. The short electron bunches that are accelerated around the storage ring are susceptible to the phenomenon of microbunching instabilities when the bunch charge exceeds a threshold. The primary feature of the microbunch instabilities is the onset of bursts of radiation in the THz range. The high frequencies involved in the emissions make detection and analysis challenging. A 60-90 GHz Schottky Barrier Diode detector was installed to investigate turn by turn evolution of the instabilities. © Published under licence by IOP Publishing Ltd.